Determinants of cooperative pig farmers' safe production behaviour in China — Evidences from perspective of cooperatives' services - Chen JI; Qin CHEN; Jacques Trienekens; Hai-tao WANG (Journal of Integrative Agriculture, 2018)
Farmers' production behaviour is a key to ensuring the safety and quality of their final products, and cooperatives play an important role in shaping that behaviour. This paper aims to explore the determinants of pig farmers' safe production behaviour, giving special focus from the perspective of cooperatives' services. This study adopted cross sectional survey data from 27 pig cooperatives and their 540 farmers in China to test the influence of cooperatives' services on farmers' safe production behaviour. The hypotheses were tested using a logit regression model. The findings indicated that although the number of services is not a key determinant of farmers' safe production behaviour, service quality matters. When a cooperative is strongly capable of involving more farmers in certain services, and provides certain services in more frequency, member farmers behave more safely. The results also show that veterinarian and pig-selling services play an important role in ensuring farmers' safe production behaviour. For this study, the quality of cooperatives' services is implied to have a positive impact on farmers' safe production behaviour. Leaders/managers of cooperatives must try to improve the quality of their services instead of merely attempting to provide a large number of services. For government officials and policy makers, designing policies that encourage cooperatives to improve their service quality is important. This research contributes to the scant literature on how cooperative services could help farmers engage in safer production behaviour, which would improve the safety of pork products in the future.